A factor-income approach to estimating grassland protection subsidy payments to livestock herders in Inner Mongolia, China. (February 2020) - Byrne, Anne T.; Hadrich, Joleen C.; Robinson, Brian E.; Han, Guodong
Highlights: Payments for ecosystem services (PES) are a popular approach to change land use and reduce environmental damage, but their efficacy relies on determining appropriate payment levels. This paper addresses gaps in the PES literature, specifically the need for approaches to estimate accurate payment levels without onerous data collection. This paper presents a factor-income approach to calculating payments to livestock producers which can be calculated using basic accounting data. The method is applied to a program which provides subsidies to sheep and goat herders in Ulanqab prefecture of Inner Mongolia, China. They are currently receiving subsidies as part of multi-billion-dollar program intended to reduce grazing and restore grassland health. Low levels of participation and insufficient grazing reductions have caused concerns about the program. This paper estimates target subsidy payments which are shown to be greater than current subsidy payments for the majority of herders in Ulanqab. This suggests that future overgrazing might be mitigated through increased subsidy payment levels. Abstract: This paper contributes to the growing literature on land use policies designed to prevent livestock overgrazing. It offers a straightforward factor-income approach to calculating payments for ecosystem services (PES) to livestock producers who reduce or suspend grazing for the purpose of grassland restoration. Our approach requires only cross-sectional farm-level accounting data and is thus feasible where policies have either not yet been applied or specialized data is sparse, as is common in many developing regions. We apply and validate this approach with empirical analysis of sheep and goat herders in the Ulanqab prefecture in Inner Mongolia, China where herders currently receive payments in exchange for reduced grazing intensity on vulnerable land. However, observed stocking rates are still commonly higher than recommended. Our results suggest payments are currently insufficient to offset the financial loss incurred by herders who reduce their grazing intensity, a finding consistent with previous studies. Using an approach we refer to as the factor-income method, we estimate and validate new levels of recommended payments. This demonstrates how future payments could be tailored to meet the financial needs of individual herding communities using basic farm-level data.